Data and code for "Tuning the lattice thermal conductivity in van-der-Waals structures through rotational (dis)ordering" - Eriksson, Fredrik; Fransson, Erik; Linderälv, Christopher; Fan, Zheyong; Erhart, Paul (Chalmers University of Technology, 2023)
This record contains neuroevolution potential (NEP) models for C, BN, and MoS2 that have been constructed to model the potential energy surfaces of these materials in the presence of interlayer rotations. It also contains databases with the results from density functional theory calculations that were used for constructing the NEP models.

Databases
The *.db files are databases with the results from density functional theory (DFT) calculations. These are sqlite databases in ase format, see here for more information. The demo-database-access.py script illustrates the most basic access.

Models
The neuroevolution potential (NEP) models described in the publication can be found in the nep-*.txt files. They can be used in conjunction with the GPUMD package. The calorine package provides a Python interface to GPUMD.

Primitive structures
Several primitive structures in extended xyz format can be found in the *.xyz files. These structures have been relaxed using the NEP models included here. The demo-for-using-structures-and-models.py script illustrates how to access the structures and models.
Keywords: neuroevolution potential; GPUMD; van der Waals materials; density functional theory; Physical Sciences; Fysik